Games Based on Simplified Neutrosophic Multiplicative Soft Sets and Their Applications - Huseyin Kamacı (Neutrosophic Sets and Systems, 2021)
In this paper, we firstly define simplified neutrosophic multiplicative soft sets by combining simplified neutrosophic multiplicative sets and soft sets. Meanwhile, we introduce some basic operations of simplified neutrosophic multiplicative soft sets and discuss their related properties. Later, we describe two person simplified neutrosophic multiplicative soft games, and give different types of solution models of these games which are simplified neutrosophic multiplicative soft saddle points, simplified neutrosophic multiplicative soft upper and lower values, simplified neutrosophic multiplicative soft dominated strategies and simplified neutrosophic multiplicative soft Nash equilibrium. Moreover, the solution models of two person simplified neutrosophic multiplicative soft games are applied to a real-world problem and supported by comparison analysis. Finally, the framework of n-person simplified neutrosophic multiplicative soft games is presented.